Clinical and Radiologic Outcomes after Cryoablation of Desmoid Tumors - Bergin, Brad; Newman, Lucas Killian; Przybojewski, Stefan (Journal of Clinical Interventional Radiology ISVIR, 2024)
Purpose This study aims to evaluate the impact of cryoablation on patients with desmoid tumors, considering both pain and functional impairment. Cryoablation has emerged as a promising intervention, primarily recognized for its ability to reduce radiological evidence of the neoplasm. However, the focus of this research is on assessing the clinical outcomes, recognizing the importance of improving patient-reported symptoms as additional evidence is required in this area to strengthen previous findings.Methods A retrospective study of 18 patients treated with cryoablation for desmoid tumors were included in this study. The evaluation of clinical status involved structured interviews to capture changes in pain and functional impairment. Pain scores and functional impairment scores were recorded on a 10-point Likert scale before and after the treatment. The correlation between these clinical findings and imaging was a key aspect of the investigation.Results Following cryoablation treatment, the average pain scores exhibited a notable decrease of 4.75 points on the 10-point Likert scale. Similarly, functional impairment scores demonstrated a significant average decrease of 4.0 points. Additionally, there was an overall decrease in viable tumor volume after ablation, correlating with the above findings.Conclusion This study provides evidence that cryoablation is effective in achieving clinically significant improvement in patients with desmoid tumors. While the reduction in radiological evidence is recognized, the emphasis of this study was on patient-reported outcomes, particularly in pain and functional impairment. These findings underscore that cryoablation is a valuable intervention in the comprehensive management of desmoid tumors improving overall quality of life.
Keywords: desmoid tumors; cryoablation